Patterns and perceptions of stone-built settlements from the Thukela Valley Late Iron Age - Maggs, T. (Southern African Humanities, 2021)
Recent work on Late Iron Age stone-built settlements in the interior grasslands of Natal is examined. Recently excavated sites largely confirm previous findings on this type of settlement and suggest that even total excavation is unlikely to give us much more information. Previously unknown rock engravings of the settlements, however, give new insight into the way in which the Iron Age inhabitants perceived the settlement pattern. To cite this article: Maggs, T. 1988. Patterns and perceptions of stone-built settlements from the Thukela Valley Late Iron Age. Annals of the Natal Museum29 (2): 417-32.